KEMAMPUAN GURU MENYUSUN BAHAN AJAR KELAS X SMA NEGERI 1 WIROSARI KABUPATEN GROBOGAN - Christianty, Devy; Alfiah, Alfiah; Sulanjari, Bambang (JISABDA: Jurnal Ilmiah Sastra dan Bahasa Daerah, Serta Pengajarannya, 2025)
This study contains the ability of teachers to prepare teaching materials for class X SMA Negeri 1 Wirosari. This study aims to describe how teachers prepare teaching materials according to the curriculum. With the formulation of the problem of how the Javanese language teacher's ability to compile teaching materials for class X SMA Negeri 1 Wirosari. This research uses a qualitative research method because the data is in the form of words, phrases and sentences, the source of the data used is teaching materials Javanese for class X SMA Negeri 1 Wirosari. Data collection techniques in the form of documentation and interviews. Data analysis techniques used are data reduction, data presentation, and conclusions. The results of this study were the preparation of teaching materials written by Mrs. Siti Nurasih, S.Pd, class X semester 2, in which there were 5 main materials, namely types of text, geguritan, wayang mahabarata, upload-ungguh basa, and pawarta according to the rules for preparing teaching materials. In this study using assessments based on content feasibility and language feasibility. Assessments on content feasibility and language feasibility used predetermined assessment instruments.